Perbandingan Model Linier Versus Analisis Vektor pada Gerak Grup Sunspot di Lintang Selatan dari Siklus Matahari Ke-23 - Nanang Widodo (Universitas Negeri Surabaya, 2013)
Comparison of the two models aimed to get a representative model that can explain the movement of sunspot groups in southern latitudes on the solar cycles 23th. If the movement of the daily sunspot groups is projected in the longitude and latitude direction, then it can considered as vector Ri. The evolution of sunspot groups during n days can be implemented into n-1 vectors and total vector of Ri is the resultant vector, R. Commonly, the movement of sunspot groups shift to positive or negative latitude direction. If R divided by a long of evolution (= n days) obtained an average vector R= (± b°B, ± l°L) where, the magnitude of b is the average difference in degrees of longitude/day, and l is the average difference in degrees of latitude/day. Distribution of sunspot group position data from firstday until to n days can be approximated by a linear regression equation. In studying the trajectory characteristics of sunspot groups used sunspot data of classes H and J in the southern hemisphere of the disk solar observations BPD Watukosek from 19972008 (cycle 23). From the comparison of the above two models obtained the best linear trajectories of a sunspot group. This result accordingly to the properties of differential rotation at the solar surface. Where at the lower latitude sunspot group will move relative faster than higer latitudes. The results of modeling can be used to interpolate to data that is not observed and extrapolated to predict the position of a sunspot group on the next day.